The Problems Of Realization of Right to Participate in Decision-Making in Environmental Matters - Kozmuliak, Kateryna (My University, 2019)
The right of citizens to participate in decision-making in environmental matters is provided by many international acts: the Rio Declaration on Environment and Development, the Aarhus Convention, the EU Directives (Directive 2001/42/EC, Directive 2003/35/EC, and Directive 2011/92/EU). A group of rights aimed at the realization of this general right are also defined in national legislation, in particular, in the Law of Ukraine “On Environmental Protection”. To comply with requirements of Annex XXX (Environment) of the Ukraine-European Union Association Agreement, there were adopted the laws of Ukraine “On environmental impact assessment” (hereinafter – the EIA Act) and “On strategic environmental assessment” (hereinafter – the SEA Act). It has led to the formation of new mechanisms of interaction between the public, business entities and authorities. However, in spite of certain achievements in ensuring the implementation of the right to participate in decision-making in environmental matters, there are a number of problems in its application in practice. They are the next: the different understanding of the concept of “public” both within national legislation and in comparison with international law; the imperfect mechanism of preventing the ignorance of the public’s position. There is no legal regulation of the ways of pre-trial settlement of the dispute, in particular, through mediation. The organization and conduction of public discussion of plans, development strategies and specific planned activities requires an improvement. The article analyzes the peculiarities of realization of the right to participate in decision-making in environmental matters, reveals the shortcomings of the current legislation, suggests ways to eliminate them.
Keywords: Ecological rights; decision-making in environmental matters; environmental impact assessment; strategic environmental assessment; mediation